PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Megawati, Megawati; Tarigan, Krisnawati (Jurnal Akuntansi Kontemporer, 2018)
The purpose of this study is to determine the effect of company characteristics on disclosure of Corporate Social Responsibility. The characteristics of the company are divided into four types, namely leverage, public ownership, the board of commis-sioners and profitability. The type of data used is secondary data. The samples comes from 129 companies in the category of companies that were awarded the Indonesia Sustainability Report Award and 130 companies that were not awarded the Indonesia Sustainability Report Award, since 2012 - 2016. The results showed that: (1) leverage as measured by Debt Ratio has no significant positive effect on disclosure of Corporate Social Responsibility, (2) Public ownership as measured by Public Share Ownership has a positive effect on disclosure of Corporate Social Responsibility , (3) board of commissioners as measured by The size of the Board of Commissioners of the company has a positive effect on disclosure of Corporate Social Responsibility , (4) profitability as measured by the value of Return On Assets has a positive effect on disclosure of Corporate Social Responsibility.